Developmental Losses in Young Children from Pre-primary Program Closures during the COVID-19 Pandemic - Alejandra Abufhele; David Bravo; Florencia López Bóo; Pamela Soto-Ramirez (Institute of Labor Economics (IZA), 2022)
The learning and developmental losses from pre-primary program closures due to COVID-19 may be unprecedented. These disruptions early in life can be long-lasting. Although there is evidence about the effects of school closures on older children, there is currently no evidence on such losses for children in their early years. This paper is among the first to quantify the actual impact of pandemic-related closures on child development, in this case for a sample of young children in Chile, where school and childcare closures lasted for about a year. We use a unique dataset collected face-to-face in December 2020, which includes child development indicators for general development, language development, social-emotional development, and executive function. We find adverse impacts on children in 2020 compared to children interviewed in 2017 in most development areas. In particular, nine months after the start of the pandemic, we find a loss in language development of 0.25 SDs.
Keywords: I25; J13; O15; Z13; 330; COVID-19; child development; Chile; childcare closures